2020
DOI: 10.1007/s00405-020-06187-1
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy, ventilatory wean, and decannulation in COVID-19 patients

Abstract: Purpose COVID-19 patients requiring mechanical ventilation can overwhelm existing bed capacity. We aimed to better understand the factors that influence the trajectory of tracheostomy care in this population to facilitate capacity planning and improve outcomes. Methods We conducted an observational cohort study of patients in a high-volume centre in the worst-affected region of the UK including all patients that underwent tracheostomy for COVID-19 pneumonitis ventilatory wean from 1st March 2020 to 10th May 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
1
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 43 publications
3
62
1
5
Order By: Relevance
“… Study Sample size Follow up period/day MV weaning %/days Decannulation % Deaths % Martin-Villares C. et al [ 9 ] 1890 a 30 days 842/1616 (52.1%) 683/1616 383/1616 (23.7%) Breik O. et al [ 10 ] 100 30 days 85/100 (85%) 84/100 mean 14 days 15/100 (15%) Angel L. et al [ 11 ] 98 Mean 11 (SD 6) 32/98 (33%) 8/98 (8%) 7/98 (7%) Yeung. et al [ 7 ] 72 Median 26 (IQR18.8–3) 44/72 61.1% median 10 days 25/72 7/72 (9.7%) Tornari C. et al [ 5 ] 78 b Median 21 (IQR 15–28) 46/69 (66.6%) 35/69 4/78 (5.1%) Picetti E. et al [ 8 ] 66 Retrospective study Mean 21.4 days (SD 7.2) N/A 15/66 (22.7%) Chao T.N. et al [ 12 ] 53 Minimum 14 days PT 30/53 (56.6%) 11.8 days (SD 6.9) 7/53 (13.2%) 16.6 days (SD 5.0) 6/53 (11.3%) Botti C. et al [ 13 ] 44 Median 22 days PI Median 35 days PI (18–79) Mean 36 (10–77) day PT 15/44 (34.1%) Floyd E. et al [ 14 ] 38 Minimum 14 days PT 21/38 (55.2%) median 10 days 7/38 (18.4%) median 14 days 2/38 (5.3%) Zuazua-Gonzalez A. et al [ 6 ] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Study Sample size Follow up period/day MV weaning %/days Decannulation % Deaths % Martin-Villares C. et al [ 9 ] 1890 a 30 days 842/1616 (52.1%) 683/1616 383/1616 (23.7%) Breik O. et al [ 10 ] 100 30 days 85/100 (85%) 84/100 mean 14 days 15/100 (15%) Angel L. et al [ 11 ] 98 Mean 11 (SD 6) 32/98 (33%) 8/98 (8%) 7/98 (7%) Yeung. et al [ 7 ] 72 Median 26 (IQR18.8–3) 44/72 61.1% median 10 days 25/72 7/72 (9.7%) Tornari C. et al [ 5 ] 78 b Median 21 (IQR 15–28) 46/69 (66.6%) 35/69 4/78 (5.1%) Picetti E. et al [ 8 ] 66 Retrospective study Mean 21.4 days (SD 7.2) N/A 15/66 (22.7%) Chao T.N. et al [ 12 ] 53 Minimum 14 days PT 30/53 (56.6%) 11.8 days (SD 6.9) 7/53 (13.2%) 16.6 days (SD 5.0) 6/53 (11.3%) Botti C. et al [ 13 ] 44 Median 22 days PI Median 35 days PI (18–79) Mean 36 (10–77) day PT 15/44 (34.1%) Floyd E. et al [ 14 ] 38 Minimum 14 days PT 21/38 (55.2%) median 10 days 7/38 (18.4%) median 14 days 2/38 (5.3%) Zuazua-Gonzalez A. et al [ 6 ] …”
Section: Resultsmentioning
confidence: 99%
“…Experts in the field suggest that applying the essential infection-control measures would lessen the viral transmissibility. As evidenced by this review, in all the tracheostomies carried out in multiple centres worldwide, regardless of the timing or the technique, none of the health care workers or hospital staff involved in the procedure, be it surgeons, anaesthesiologists or nurses, reported any symptoms and/or demonstrated seroconversion within 2 weeks of this procedure, provided that they all followed the guidelines and committed to the use of appropriate PPE and adhered to strict donning and doffing procedures [ [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of our study show that SOFA at ICU admission, with a cut-off point of 4.5, was the only variable associated with the need for tracheostomy due to PMV. Tornari et al [ 29 ] found that higher FiO 2 (≥ 0.4) at tracheostomy and peak cough flow prior to tracheostomy were associated with delayed decannulation in COVID-19 patients. Different studies conducted in non-COVID-19 patients have been published assessing predictors of PMV, [ 30 ] showing that variables that evaluate the severity of critical illness, most of them included in the SOFA score, could predict the need for PMV and tracheostomy.…”
Section: Discussionmentioning
confidence: 99%
“…Tornari and colleagues conducted an observational cohort study to understand the factors that influenced the trajectory from tracheotomy to decannulation to facilitate ICU capacity planning and improve outcomes. Higher FiO 2 at tracheotomy time and higher pre-tracheotomy peak cough flow were associated with longer delays in decannulation of COVID-19 tracheotomy patients (25).…”
Section: Discussionmentioning
confidence: 99%